Direct maintenance cost prediction of civil aircraft. Issue 5 (26th August 2014) - Wang, Huawei; Gao, Jun; Wu, Haiqiao
Abstract : Purpose: – The purpose of this paper is to analyze parameters that influence direct maintenance cost (DMC) in the civil aircraft operational phase. Reducing direct maintenance cost of civil aircrafts is one of the important ways to improve economy. DMC prediction can provide decision support for the optimization of the design parameters optimization to realize the objection in decreasing the maintenance cost, and it can also improve the aircraft competitiveness. Design/methodology/approach: – The paper analyzes some parameters comprehensively, which influence DMC in the civil aircraft's operational phase. Based on the analysis of the influential parameters and the characteristics of data in the period of civil aircraft's designing period, the paper presents prediction support method based on fuzzy support vector machine (FSVM) and realizes quantitative forecast of DMC in the aircraft design phase. Findings: – The paper presents the process of DMC analysis and model in the aircraft design phase, the DMC prediction model is used in newly developed aircrafts. Practical implications: – The numerical examples using B737NP fleet data in the paper have proved the effectiveness of the proposed method. Originality/value: – The paper establishes the prediction model of civil aircraft DMC based on FSVM. The model can handle fuzzy data and small sample data which contain noise. The results prove that the method can satisfy the demand of the real data in civil aircraft designing.